Improving Second Semester Students’ Speaking Ability Through Storytelling Learning Modelat English Study Program of Timor University (A Classroom Action Research Method) - Yohanes Paulus Florianus Erfiani (Metathesis: Journal of English Language, Literature, and Teaching, 2017)
The aim of this research is to increase the students’ speaking ability through storytelling model in Universitas Timor, Timor Tengah Utara Regency (TTU), East Nusa Tenggara, Indonesia. The main purpose of this research is to know the improvement of many aspects in speaking ability such as grammatical aspect, vocabulary aspect and pronunciation aspect. This research used class action research. The subject of the research is the second semester of English education in A class in the academic year of 2016/2017. There were 30 students for the research subject. Based on the data analysis, there is a significance improvement in each cycle. The average of students’ speaking ability in Cycle I is 67%. That average is taken from vocabulary aspects 68%, pronunciation aspect 67% and grammatical aspect 66%. Then, in cycle II the average of student’s mark is increasing into 81% that consist of vocabulary aspect 83%, pronunciation aspect 795 and grammatical aspect 81%. Therefore, this research indicates that storytelling model can improve the speaking ability of second semester students in Uiversitas Timor.Kata Kunci: Storytelling model, improving speaking ability